2016
DOI: 10.1097/mnm.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Value of fourth and subsequent post-therapy follow-up 18F-FDG PET/CT scans in patients with breast cancer

Abstract: Objective To evaluate the accuracy and value of the fourth and subsequent post-therapy follow-up fluorine-18 fluorodeoxyglucose (18F-FDG) PET/computed tomography (CT) scans in the clinical assessment of breast cancer patients. Materials and methods Ninety-two female patients, with a total of 426 fourth and subsequent follow-up PET/CT scans, were retrospectively included. Patients were followed for a median of 23.7 months (range, 0.7–124.4) from the fourth follow-up PET/CT. The diagnostic accuracy of PET/CT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The diagnostic sensitivity, specificity, PPV, NPV and accuracy of the 134 scans were 93.3%, 99.2%, 93.3%, 99.2% and 98.5%, respectively, which showed comparable diagnostic performance to our study except in PPV (93.3% vs. 69% in our study). They categorized indeterminate findings (FDG-avid lesions, but not clearly identified as recurrence) as 'negative', which may lead to higher PPV values than those in our study [4]. In our study, the sensitivity and NPV were 100%, which means that negative findings of surveillance PET/CT might be also clinically valuable by reassuring that a patient did not have recurrence or another malignancy.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The diagnostic sensitivity, specificity, PPV, NPV and accuracy of the 134 scans were 93.3%, 99.2%, 93.3%, 99.2% and 98.5%, respectively, which showed comparable diagnostic performance to our study except in PPV (93.3% vs. 69% in our study). They categorized indeterminate findings (FDG-avid lesions, but not clearly identified as recurrence) as 'negative', which may lead to higher PPV values than those in our study [4]. In our study, the sensitivity and NPV were 100%, which means that negative findings of surveillance PET/CT might be also clinically valuable by reassuring that a patient did not have recurrence or another malignancy.…”
Section: Discussionmentioning
confidence: 50%
“…It is well-known that fluorine-18 fluorodeoxyglucose (FDG) PET/CT is the most valuable imaging modality in detecting recurrence or metastasis in patients with breast cancer with documented or suspected recurrence detected at physical, laboratory, or other conventional imaging examinations [3][4][5]. With excellent diagnostic sensitivity and accuracy, FDG PET/CT can provide clarification on whether the recurrence is isolated, which potentially alters treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indications were categorized in 4 groups: PET/CT for diagnosis of tumor recurrence (303/1,659, 18.3%), PET/CT before starting therapy for tumor recurrence (64/1,659, 3.9%), PET/CT to assess therapy response for tumor recurrence (507/1,659, 30.6%), and follow-up PET/CT after completion of treatment for tumor recurrence (785/1,659, 47.3%). Overall, fourth and subsequent follow-up 18 F-FDG PET/ CT scans resulted in change in management in 31.6% of the scans (356 of 1,128) when the scans were obtained for medical necessities (indications [1][2][3][4][5][6][7][8][9][10][11], and in 5.6% of the scans (30/531) when the scans were obtained without any medical necessity (indication 12). Conclusion: The fourth and subsequent PET/CT scans obtained after completion of primary treatment led to a change in management in 31.6% of the scans when acquired for appropriate clinical reasons.…”
mentioning
confidence: 99%
“…Any additional follow-up 18 F-FDG PET/CT scans (beyond 3) will be covered only at the discretion of local Medicare administrative contractors, justified by a medical necessity (6). Previously, we evaluated the role of fourth and subsequent follow-up 18 F-FDG PET/CT scans obtained after primary treatment completion, in different cancers, and the results showed that 18 F-FDG PET/CT significantly affects the management of these patients especially when there is clinical suspicion of recurrence before performing the scans (7)(8)(9)(10). This study aimed to investigate the common indications of medical necessity to perform a fourth and more follow-up 18 F-FDG PE/CT scans, which may have high impact on the management of patients with different cancers.…”
mentioning
confidence: 99%